Case report: A case of spinal muscular atrophy in a preterm infant: risks and benefits of treatment - Elisa Nigro; Eyal Grunebaum; Binita Kamath; Christoph Licht; Caroline Malcolmson; Aamir Jeewa; Craig Campbell; Hugh McMillan; Pranesh Chakraborty; Mark Tarnopolsky; Hernan Gonorazky (Frontiers in Neurology, 2023)
Spinal muscular atrophy (SMA) is a neuromuscular genetic disorder caused by the loss of lower motor neurons leading to progressive muscle weakness and atrophy. With the rise of novel therapies and early diagnosis on newborn screening (NBS), the natural history of SMA has been evolving. Earlier therapeutic interventions can modify disease outcomes and improve survival. The role of treatment in infants born preterm is an important question given the importance of early intervention. In this study, we discuss the case of an infant born at 32 weeks who was diagnosed with SMA on NBS and was treated with Spinraza® (Nusinersen) and Zolgensma® (Onasemnogene abeparvovec-xioi) within the first 2 months of life. With the scarce evidence that currently exists, clinicians should be aware of the efficacy and safety impact of early therapy particularly in the preterm infant.